In Silico Prediction of Potential Compounds of Nigella sativa as Aromatase Agonists and Ability to Cross the Blood-Brain Barrier for treatment of Alzheimer’s Disease - Kusuma Andriana; Nurdiana; Wisnu Barlianto; I Wayan Arsana Wiayasa; Masruroh Rahayu (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Alzheimer’s disease (AD), is a chronic neurodegenerative disease which condition ischaracterized by a decline in memory, thinking skills, and the ability to perform basic activities of dailyliving. Study showed that postmenopausal women with AD had a lower aromatase activity (p450 aromatase)in the brain compared to menopausal women without AD. To improve cognitive function in AD patients,Nigella sativa (NS) was found to have a protective effect on memory, and cognitive function. This studytherefore, aimed to investigate in silico prediction of potential compounds of Nigella sativa as aromataseagonists and ability to cross the Blood-Brain Barrier (BBB) for treatment of Alzheimer’s Disease. Methods:The data sets used in this study were collected from databases KnapSack Kanaya, PubChem, and PASSserver Way2Drug. HitPick and Autodock Vina was performed. Additionally, the systematic analysisinvolved ADMET, LMMD, and SWISS ADME. Results and Discussions: In silico test results revealed themost promising constituents in 36 active NS compounds that may have potential to reduce the severity ofthe AD, owing to its anti-inflammatory, cytochrome p450 stimulants, free radical scavengers, antioxidants,and immunomodulators. The ability of NS to cross the BBB was proven by admetSAR LMMD with ananalysis average value of 0.91 (from the highest value of 1). Further, NS can trigger cytochrome P450aromatase activity via Quercetin 3-(6’’ ‘’-feruloylglucosyl)-(1->2)-galactosyl-(1->2)-glucoside which has abetter binding affinity value than its control (androstenedione). NS through oleic acid compounds may bindto peroxisome proliferator-activated receptor gamma (PPRAG), similar to Rosiglitazone which may affecttranscription and activation regulation of PPARG. Conclusion: To be concluded, Nigella sativa could beused as a potential medicinal plant for the treatment of Alzheimer’s disease.